Children’s Social Desirability: Effects of Test Assessment Mode - Miller, Patricia H. (Pers Individ Dif, 2015)
This study examined a recently developed short version of the Children’s Social Desirability (CSD-S) scale with 157 fourth-grade children. Of interest was a) whether one-month test-retest reliability would vary as a function of test assessment mode (interview or classroom), gender, race, SES, and BMI percentile, and b) whether the degree of social desirability would vary as a function of these same variables. The CSD-S scale showed good test-retest reliability for both interview and classroom assessment modes (.85 and .83, respectively). Internal consistency also was good (first interview administration = .84; first classroom administration = .81). Reliability was good and did not vary significantly over assessment mode or any child subgroup variables, suggesting that the CSD-S scale is appropriate for general use. The interview mode elicited significantly more socially desirable answers than did the classroom mode. Social desirability did not differ across child subgroups. Some of these findings were examined, and replicated, on another sample. Thus, the CSD-S scale may be used with diverse groups of children to a) reliably assess a social desirability bias that may systematically bias other self-reports of interest to researchers and b) examine individual differences in degree of social desirability.